Emotion recognition - 1 - Muhammad Farhan Othman (2017)
Emotion recognition has become an emphasising research area since it plays an important role in the human computer interaction paradigm. However, emotions can be complex which makes it challenging for machines to perceive various facial expressions. Unlike humans, machines require a much subtle approach in order to classify a facial expression correctly.